Inovasi Pemasaran dan Pendampingan Penyusunan Laporan Keuangan Dengan Aplikasi “SI APIK” pada UMKM Roti Maryam “NULIN” - Pipin Fitriasari; Fara Annisa Syam; Siti Masyitah; Sofia Maulida (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
This community service activity in the form of mentoring for MSMEs in Gunung Sari Ulu Village aims to provide understanding to MSME actors in Gunung Sari Ulu Village about the importance of brands and packaging in a product and the need for digital financial management and digital marketing (online). MSME mentoring activities are carried out to innovate Maryam bread products "NULIN" such as: providing new packaging; and digital financial management training with the "SI APIK" application. With the mentoring activities, it is hoped that it can attract public attention to the product and also reach a wider market.